Diversidade genética de receptores de lactoferrina e transferrina em Moraxella bovis e Moraxella bovoculi - Espíndola, Julia Pires (2021)
Infectious bovine keratoconjunctivitis (IBK) is the most important eye disease in cattle, which has a great economic impact due to eye injuries and loss of vision, resulting in pain, reduced milk production, and decreased weight gain. The main etiological agents associated with IBK are Moraxella bovis (M. bovis) and Moraxella bovoculi (M. bovoculi). Vaccination is essential for the disease control; however, currently available vaccines may present limited efficiency. Moraxella spp. have systems capable of extracting iron from the host glycoproteins named lactoferrin and transferrin. Each receptor is composed of an integral outer membrane protein, named lactoferrin or transferrin binding protein A (LbpA or TbpA), and of exposed surface lipoprotein, named lactoferrin or transferrin binding protein B (LbpB or TbpB). These receptors are known to be functionally and genetically related and are known for being essential in the maintenance of pathogens on the mucosal surface leading to disease development. Studies involving immunization with antigens derived from these receptors demonstrate a great capacity to prevent infection, as well as to eliminate colonization of the upper respiratory tract. A great potential of these receptors as vaccine antigens is expected due to their privileged position on the cell surface, and their presumed ubiquity in all isolates of Moraxella spp. However, to date, there have been no studies on the diversity of the pathogens responsible for IBK, or they have been investigated as potential vaccine compounds. In this context, this thesis was designed to investigate the genetic diversity and its distribution in the structure of TbpA and TbpB proteins of M. bovis and M. bovoculi (manuscript 1) and the diversity of LbpA, as well as the development of hybrid antigens (manuscript 2). For manuscript 1, DNA sequences of thirty-seven M. bovis and M. bovoculi strains were translated into amino acids to build phylogenetic trees for each protein. The alignments were then mapped on the predicted structures of the proteins. In the phylogenetic analysis, TbpB sequences were separated by species and more variable than TbpA. Also, two representative strains of TbpB were selected that are likely to be able to cover all the variability found in these strains. In manuscript 2, a similar analysis was performed with thirty-six LbpA sequences, and five hybrid antigens were constructed using four different combinations of LbpA loops in a scaffold of the surface lipoprotein from Vibrio cholerae (VcSLP). LbpA was very conserved also throughout its whole structure. Hybrid antigens were expressed on a small scale efficiently and had the potential to be large scaled for analysis of immunogenicity and cross-reactivity as vaccine antigens. In conclusion, it was demonstrated in two different studies the diversity of TbpA, TbpB, and LbpA and the approaches that can be taken to produce vaccine antigens derived from these proteins intending to cover all the genetic diversity of the species.